Vegetative compatibility and pathogenicity of Verticillum dahliae isolates from olive (Olea europea) - A. Tantaoui (Phytopathologia Mediterranea, 2002)
Vegetative compatibility, determined by pairing auxotrophic mutants that are unable to utilize mineral nitrogen, was studied by means of 44 isolates of Verticillium dahliae Kleb. Thirty-seven isolates were collected from olive in the main areas in Morocco, 3 from Algerian olives, 2 from tomato, 1 from aubergine and 1 from olive-grove soil where Verticillium wilt was present. Approximately 475 mutants were used, allowing assignment of 34 isolates to 3 vegetative compatibility groups (VCGs). The VCGs of the remaining 10 isolates were not defined. The pathogenicity of ten isolates was assessed by inoculating olive plants with suspensions of conidia at 105 conidia ml-1. Highly significant differences in the pathogenic ability of the ten isolates were recorded. No relationship was found between VCGs and pathogenicity of isolates.